Penerapan Pembelajaran Berdiferensiasi untuk Meningkatkan Hasil Belajar Sepak Bola - Joan Rhobi; Prasetiyo, Rahayu (S&Co Publishing, 2025)
This study aims to determine the effect of differentiated instruction on improving the learning outcomes of basic football techniques among fifth-grade elementary school students. The research employed a quantitative approach with a pre-experimental one-group pretest-posttest design. The subjects consisted of 30 students selected through total sampling. Data were collected using a basic football skills test administered before and after the implementation of differentiated learning. Descriptive statistical analysis showed an increase in the average score from 61.83 (pretest) to 75.00 (posttest). The paired sample t-test yielded a t-value of -37.341 with a significance level (p-value) of 0.000 (p < 0.05), indicating that the difference was statistically significant. The results conclude that differentiated instruction is effective in enhancing students' learning outcomes in basic football techniques. This finding suggests that physical education teachers should implement instructional strategies tailored to the abilities and characteristics of their students